The Effects of Brand Image and Price on Purchase Decision of Vivo Smartphones in Pampangan District - Sofi Tamara; Juhaini Alie; Muhammad Wadud (International Journal of Marketing & Human Resource Research, 2021)
This study aims to investigate the effects of brand image and price on purchasing decisions for Vivo cell phones at Renni Cell Pampangan outlets, Ogan Komering Ilir Regency (OKI). Measurement of the sample used the Slovin formula with a final total of 53 respondents. Data were analyzed using the multiple linear regression method. Partially, the results evidence that each brand image and price affects purchasing decisions. Simultaneously, brand image and price influence purchasing decisions. This research is beneficial for the smartphone brand Vivo. To market its products, especially in the demographics outside the city, Vivo must consider brand image and price because these two factors influence purchasing decisions.